Preparation of antibacterial silk fibroin membranes via tyrosinase‐catalyzed coupling of ε‐polylysine. (29th May 2015) - Wang, Ping; Deng, Chao; Yuan, Jiugang; Yu, Yuanyuan; Cui, Li; Su, Mengting; Wang, Qiang; Fan, Xuerong
Abstract: Silk fibroins have good biocompatibility and could be used to form a variety of regenerated functional biomaterials. In this study, enzymatic oxidization of silk fibroins with tyrosinase (TYR) was carried out, followed by coupling of ε‐polylysine (ε‐PLL) for improving antibacterial ability of the fibroin‐based biomaterial. Trinitrobenzene sulfonic acid (TNBS) was selectively used to incubate with silk fibroins prior to TYR treatment, aiming at preventing the self‐crosslinking of silk fibroins during enzymatic oxidation. The results indicated that tyrosine residues in silk fibroins could be converted to reactive dioxyphenylalanine and o ‐quinone residues TYR successively. TNBS pretreatment inhibited the self‐crosslinks of silk fibroins and promoted the successive coupling of ε‐PLL to fibroin proteins with high graft yield. The combined use of TNBS, TYR, and ε‐PLL treatments endowed fibroin membrane with satisfactory antibacterial ability against Staphylococcus aureus, and the obtained durability was also acceptable. The changes in surface potential and amine acid composition for the fibroin membranes verified the favorable actions of the combined treatment. The present method could be potentially utilized for enzymatic functionalization of various fibroin‐based biomaterials.